Factors influencing the seasonal abundance of Aedes (Stegomyia) aegypti and the control strategy of dengue and dengue haemorrhagic fever in Thanlyin Township, Yangon City, Myanmar - Oo, Thin Thin; Storch, Volker; Madon, M. B.; Becker, Norbert (Tropical biomedicine, 2011)
From June 2006 to May 2007, mosquito surveys were conducted in Thanlyin Township, Yangon City, Myanmar, to determine factors influencing the abundance of Aedes aegypti (Stegomyia aegypti) during the rainy season. Both the biological and environmental factors were included in this study. Increase in the hatchability of egg, larval survival rate, the shortened larval life-span and increased pupation rates supplemented by rainfall (i.e. continuous flooding of the containers, stimulate the continuous hatching of eggs) were observed for correlation with the increase in population density of Ae. aegypti during the rainy season in the study area. Control strategy of Ae. aegypti to analyze the infestation in the community (study area) with larval Ae. aegypti, integrated management measures including health education, attitudes and practices regarding dengue and dengue haemorrhagic fever, transmission of the disease and possible preventive measures, reduction of breeding sites and testing the efficacy of Bacillus thuringiensis israelensis (B.t.i.) with respect to the reduction level of Ae. aegypti larvae in breeding sources, were taken into consideration.